Al Jam’iyatul Washliyah's Digital Dawah to Responding Challenges of 5.0 Era - M. Rozali (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
This study aims to map the ideal da'wah model in the Al Jam'iyatul Washliyah organization with the title Al Jam'iyatul Washliyah's Digital Dawah to Responding Challenges of the 5.0 Era. The objectives of this study: 1. How are the methods and media of Al Jam'iyatul Washliyah's dawah? 2. How is the relevance of Al Jam'iyatul Washliyah's dawah media? This study uses the Krippendorff’s Qualitative Content Analysis measurement model, a research technique that can produce conclusions that can be replicated or validated while still considering the context. Content analysis is a research technique that produces various conclusions by systematically and objectively identifying the specific characteristics of a text. Six steps in analyzing content are: Unitization, sampling, recording or coding, reduction, inference, and narration. The findings of this study are: 1. The method of dawah Al Jam'iyatul Washliyah is with wisdom, mau'izah al-hasanah, and mujadalah billati hiya ahsan. The dawah media of Al Jam'iyatul Washliyah are: a. Oral Media, b. Written Media, c. Amali Media. 2. Al Jam'iyatul Washliyah's dawah is still relevant in society, but it is necessary to improve the methods, models, media and techniques more modern. This dawah model is important to discuss with the arguments: 1. Dawah is the spirit of Islam, without dawah activities Islam will not develop to areas that are difficult to reach and even feared will die. Remote areas are vulnerable points to the death of Islamic teachings and sharia if they do not receive serious attention, especially throughout Indonesia in general and the remote areas of North Sumatra in particular. 2. Serious efforts are needed to update the developments of the times and always upgrade every device in the organizational structure of Al Jam'iyatul Washliyah and even be able to create new prototypes or models in dawah if they do not want to be left behind.